KEMISKINAN, PENDIDIKAN, DAN AKSES LAYANAN KESEHATAN DI INDONESIA - Haura Sabitta Zikra Loen; Sabita Alya Siti Azahra; Herni Yulianti; Olivia Nur Fatimah; Permata Indah Sari; Ishfa Nur Azizah; Adinda Triani Rahma Putri; Nanang Martono (JURNAL EDUCATION AND DEVELOPMENT, 2024)
Health issues are still a major problem all over the world. Health issues include the quality of health services and issues of social inequality in the provision of health facilities. Some people who suffer from health complaints have difficulty accessing health care, one of them on the outpatient health facility. The availability of health care facilities affects people's decision to do treatment when they are get sick. The study aims to analyze factors that influence the population's decision not to take medication when ill, such as: poverty levels, education levels, and the number of health facilities. This research uses methods of quantitative secondary data analysis. Data obtained from BPS in 2023. Data analyzed using product moment correlation calculations. The variables analyzed are the percentage of the population that has health complaints and does not take medication (Y); the percent of the poor population (X1); the level of education (X2); the proportion of the number of health facilities (X3). Based on the results of the study, the ratio of the percentage of the poor population with the main reason not taking medication because there are no transportation costs is significant. The ratio between the percentage of the poor population with the main reason not taking medication because there is no transportation facilities is significant. The ratio between elementary school GER with the main reason not taking medication because there are no transportation costs is significant. The ratio between the percentage of the number of health facilities with the main reason not taking medication because due to long waiting times for sevices.